ANALISIS KEBERLANJUTAN USAHATANI PADI SAWAH DI KECAMATAN SOREANG KABUPATEN BANDUNG - Gilang Fauzi Dzikrillah; Syaiful Anwar; Surjono Hadi Sutjahjo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Rice farming in Soreang district of Bandung Regency face problems that pose a threat to the sustainability of food security. This research objectives is to analyse and assess the sustainability of rice farming in Soreang District with Rapid Appraisal Usahatani Padi (RAP-FARM) using Multidimensional Scaling (MDS) method. Results shows rice farming in Soreang District assessment using RAP-FARM yield 49.07 in sustainability index which can be categorized as less sustainable. Leverage analysis results showed that out of 48 existing attributes, 21 sensitive attributes proven to have influence on the rice farming sustainability index. The perspective analysis shows that there are 6 key factors that have significant influence on wetland rice farming which are: (1) conformity of land usage to the land properties, (2) farmers motivation, (3) organic material usage and utilization of farm waste, (4) freedom from pest infestations and diseases, (5) land fertility, and (6) usage of chemical pesticides. The efforts for improving rice farming in Soreang Regency require a sustainability index value by way of managing and repairing sensitive attributes with attribute 21 focus on improvements of the sensitive 6 key factors attribute against the rice farming.